2014
DOI: 10.1038/ncomms5536
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear in situ magnetic resonance imaging of electrochemical double-layer capacitors

Abstract: The last decade has seen an intensified interest in the development and use of electrochemical double-layer capacitors, fuelled by the availability of new electrode materials. The use of nanoporous carbons, in particular, with extremely high surface areas for ion adsorption has enabled the development of working devices with significantly increased capacitances that have become viable alternatives to lithium-ion batteries in certain applications. An understanding of the charge storage mechanism and the ion dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…7,8 However, historically, MRI of bulk metals has been very rare (as detailed in supplementary material Section S2), due to challenges posed by the physics of propagation of radiofrequency (r.f.) magnetic field (B 1 ) in bulk metals.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, historically, MRI of bulk metals has been very rare (as detailed in supplementary material Section S2), due to challenges posed by the physics of propagation of radiofrequency (r.f.) magnetic field (B 1 ) in bulk metals.…”
Section: Introductionmentioning
confidence: 99%
“…experiments to enable independent yet simultaneous observation of both electrodes. 77 Using in situ MRI, the electrodes can be studied individually in the standard 'parallel plate' geometry, without the need for the shifted cell design. By using a specially-designed PTFE cell and deuterated solvent, …”
Section: In Situ Nmr Of Supercapacitors: Experimental Considerationsmentioning
confidence: 99%
“…Imaging results can also be combined with spectroscopic information provided by NMR, providing spatially resolved chemical information. Recently, Ilott et al [16]presented the first in situ experiments showing localized information of the electrolyte ions in real time for a working capacitor of standard geometry. It has also been shown that MRI is able to map concentration gradients and visualise electrochemical processes in electrochemical cells containing bulk metals [17].…”
Section: Introductionmentioning
confidence: 99%